Neural mechanisms underlying synchronization of movement to musical cues in Parkinson disease and aging - Harrison, Elinor C.; Grossen, Sarah; Tueth, Lauren E.; Haussler, Allison M.; Rawson, Kerri S.; Campbell, Meghan C.; Earhart, Gammon M. (Frontiers in Neuroscience, 2025)
IntroductionExternal and internal musical cues provide therapeutic techniques for gait rehabilitation in aging and neurological disorders. For people with Parkinson disease (PwPD), mental singing is a type of internal cue that can regularize gait timing. No studies to date have directly measured brain activity during external and internal musical cues as used in gait rehabilitation. Evidence suggests the neural mechanisms of external vs. internal cued movement differ. External cues are thought to drive movement via recruitment of cerebello-thalamo-cortical (CTC) pathways, while internal cues are thought to rely more on striato-pallido-thalamocortical (SPT) pathways.MethodsWe investigated the neural mechanisms that underlie acute responses to external cues (listening to music) and internal cues (mental singing). Using fMRI, we imaged PwPD and age-matched healthy controls (HC) while performing finger tapping during musical cueing tasks.ResultsNo differences were seen between PwPD and HC in any of the comparisons. Functional imaging results showed activation of sensorimotor cortex, temporal gyri, supplementary motor areas, and putamen for both cueing tasks. External cues additionally activated auditory cortex while internal cues additionally activated the cerebellum. When directly comparing cue types, external cues displayed greater activity in the primary auditory cortex and temporal gyri.DiscussionThese results suggest similar brain regions are activated during musically-cued movements for both PwPD and HC and both cue types utilize parallel pathways for processing. Both cue types may facilitate use of remaining function of areas that degenerate in PD (e.g., putamen) and potentially also activate routes through less impaired areas (e.g., cerebellum). This supports the idea that the CTC and SPT pathways work in tandem and facilitate sensorimotor activity via a complex interplay between neural circuits. These findings have implications for how external and internal cues may be administered in future therapies.